Effects of Dietary Inclusion of an Omega-3 Fatty Acid-based Supplement on Biological Parameters and Sperm Characteristics of Developing Beef Bulls - Allen G. Schwartz (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: This study was to evaluate the impact of including an omega-3 fatty acid-based supplement in the diet of developing beef bulls on growth and semen characteristics. Study Description: Weaned beef bull calves (n = 39) from the Kansas State Purebred Beef Unit were supplemented with an omega-3 based fatty acid-based supplement through one of three dietary treatments: 0.00 (CON), 0.48 (MOD), or 0.96 (HI) lb/head/day (dry matter basis; extruded flaxseed and algae-based supplement, Better Fed Foods/NBO3, Manhattan, KS). Treatments were applied for 80 days in precision intake management bunks, allowing for the monitoring of performance data. Bulls were evaluated for semen characteristics through breeding soundness exams conducted three times throughout the trial. The Bottom Line: Results suggest that omega-3 supplementation may impact sperm cell motility in young bulls within the inclusion levels and duration of this experiment, which may ultimately help counter the negative effects of overfeeding on semen quality.
Keywords: developing bulls; fertility; omega-3